VILLAGE-OWNED BUSINESSES AS A STRATEGY TO ENHANCE THE LOCAL ECONOMY IN SEDAPURKLAGEN VILLAGE, GRESIK, EAST JAVA - Imamah, Nurul; Rahmasari, Anggraeni; Noviandari, Indah; Iradawaty, Sofiah Nur; Gintara, Mohammad Yoga (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The purpose of this research is to analyze the role and impact of BUMDes (Village-Owned Businesses) in enhancing the local economy of Sedapurklagen Village, Benjeng, Gresik, East Java, Indonesia. This field-based study utilizes triangulation techniques including observation, interviews, and documentation, and employs a qualitative descriptive approach. The findings demonstrate that BUMDes plays multiple significant roles in improving the community's economy. It acts as a facilitator, assisting in all tasks related to planning business entities to be established by the community. Furthermore, BUMDes also serves as a mediator, facilitating the management of business entities to achieve business goals and plans, and acts as a motivator by spearheading and inspiring business entities to drive community improvement. One challenge faced by BUMDes management in Sedapurklagen Village is the need to build more trust within the community and managing limited available capital. In order to gain community trust, BUMDes must provide tangible evidence. Communities that have faith in BUMDes can aid in convincing other communities, while the younger, more educated village members can assist in promoting the understanding of BUMDes to communities that are not yet familiar with its functions.